Java and Mac OS X - Davis, Gene. (Hoboken, N.J. : Wiley Pub., 2010)
Provides information on creating Java applications for Mac OS X, covering such topics as Xcode, porting and designing, embedding Cocoa components, understanding JNI, creating terminal applications, and integrating Java controllers.
Introduction -- Getting started. Programming Java for OS X ; Introducing the environment ; Understanding Xcode ; Building basic projects ; Deploying applications -- Bringing guidelines, APIs, and languages together. Porting and designing ; Integrating windows, menus, and dialog boxes ; Embedding cocoa components -- Architecting alternative applications. Understanding JNI ; Creating screen savers ; Creating terminal applications.
Print version record.
English.
John Wiley and Sons
Keywords: Mac OS; Mac OS; Mac OS; Mac OS (Computer software); Java (Computer program language); Java (Langage de programmation); COMPUTERS -- Programming Languages -- JavaScript; COMPUTERS -- Programming Languages -- VBScript; Java (Computer program language); Java (langage de programmation); Macintosh (Computer) -- Computer software; Java (Computer language)